Pengaruh Content Marketing Terhadap Keputusan Berbelanja Online Dengan Customer Engagement Sebagai Variabel Mediasi Pada Pengguna Platform Live Shopping Di Kota Padang - Mona Lisa; Yofina Mulayati (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of content marketing on online shopping decisions with customer engagement as a mediating variable among users of live shopping platforms in Padang City. The rapid development of digital technology has encouraged the widespread use of live shopping features, which offer real-time interaction between sellers and consumers. As a result, content marketing strategies play a crucial role in attracting attention and influencing consumers' purchasing decisions. This research uses a quantitative method with data collected through questionnaires distributed to 138 respondents who are active users of live shopping platforms in Padang City. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 3.0 software. The results show that content marketing has a positive and significant effect on both customer engagement and online shopping decisions. Furthermore, customer engagement also has a positive and significant impact on online shopping decisions. In addition, customer engagement is proven to mediate the relationship between content marketing and online shopping decisions. These findings indicate that effective and interactive content marketing strategies can enhance consumer engagement and drive purchasing behavior.